Vascular flora of Zarrin-Kuh Protected Area in Central Kopet Dagh Mountains, NE Iran: An annotated checklist - Amiri, Mohammad Sadegh; Saeidi Mehrvarz, Shahryar; Memariani, Farshid; Joharchi, Mohammad Reza (Phytotaxa, 2022)
Zarrin-Kuh Protected Area (ZPA) is a part of the Khorassan-Kopet Dagh floristic province of the Irano-Turanian region. In this research, we present the first checklist of vascular plants of ZPA along with the life-form spectrum, phytogeography, and conservation status. We conducted field surveys through several random collection efforts and vegetation sampling during 2015–2017. A total of 549 species/infraspecific taxa belonging to 69 families and 318 genera are recorded as native and naturalized plants. The most prominent families are Asteraceae (43 genera/72 species), Poaceae (29/44), Brassicaceae (31/43), Fabaceae (15/43), and Chenopodiaceae (24/41). The richest genera are Astragalus (21 taxa), Euphorbia (10), Acanthophyllum (8), and Allium (8). The therophytes (47.2 %) and hemicryptophytes (25.2%) are dominant in the life-form spectrum. Irano-Turanian elements (347 taxa, 63.2%) are the most common plants; however, the area is inhabited by several Iranian and/or Khorassan-Kopet Dagh endemic, rare and narrow-range plants, among which 17 species are threatened. Astragalus androssovianus Gontsch. is also recorded as new to the flora of Iran. Over-grazing and exploiting valuable plants are the most critical threats to the area. The results support more effective protection practices to ensure the conservation of the unique flora of Central Kopet Dagh.